PERAN PABRIK SAGU HAKIM DALAM MENINGKATKAN PENDAPATAN KARYAWAN DITINJAU PERSPEKTIF EKONOMI SYARIAH DI DESA SEBANGUN KECAMATAN SEBAWI - Reza, Rizqi; maskupah; Marina (Cross-Border Journal of Business Management, 2025)
Every factory has the potential to be developed, in its development the role of employees is needed to achieve the goal of optimal local resource processing both in terms of natural resources and from the potential possessed by each employee. This research is a type of descriptive qualitative research with a type of research, namely field research (library research). The data collection techniques used are observation, interviews and documentation. The data sources used are primary data and secondary data. Data analysis techniques in the study used data reduction, data presentation and conclusion drawn. The data validity technique used is source triangulation. The results of this study show that the role of the Hakim sago factory in increasing employee income is said to be good and achieved by the fulfillment of the three roles of the Hakim factory, namely helping to improve the employee economy; conducting employee coaching; participate in MSME funding. This study also shows that the role of the Hakim factory in increasing employee income reviewed from the perspective of Sharia Economics in Sebangun village, Sebawi District is said to be fulfilled as evidenced by increasing the living rate of employees, the fulfillment of employee needs, and the openness of the sago factory with the local government. There is employee participation in terms of developing village potential. Participation in sago festival activities is a characteristic of Sebangun village, Sebawi District.